Exploration of communication gaps among women with metastatic breast cancer, caregivers and oncologists. (October 2016) - Citron, Marc L; Mayer, Musa; Dickson, Robyn Bell; Jones, Stephen; Brufsky, Adam M
Aim: The Make Your Dialogue Count survey aimed to explore communication gaps between patients/caregivers and oncologists, and the needs of patients/caregivers at diagnosis and most recent treatment change.Methods: Three distinct sets of parallel questions were asked of 359 women with metastatic breast cancer, 234 caregivers and 252 oncologists. Survey respondents were not necessarily associated with each other.Results: Patients/caregivers considered themselves knowledgeable, yet many lacked basic disease information affecting treatment decisions. Patients/caregivers reported that oncologists do not discuss important topics at diagnosis. Patients failed to discuss side effects, but wanted their oncologist's help to manage side effects.Conclusion: This survey provides additional insight on interactional dynamics to bridge gaps in understanding that affect quality of care.